A Puzzle about Belief-about. Issue 520 (13th January 2021) - Rausch, Alex
Abstract: I present a puzzle for the standard, propositional semantic account of belief reports by considering novel inferences which it incorrectly predicts to be invalid under assumptions that are plausible by its advocates' own lights. In response, I propose a conservative departure from the standard view on which certain 'that'-clauses designate novel devices of semantic type < e, t > that I call open propositions . After outlining some desiderata for a theory of open propositions, I provide some reasons for advocates of the standard view to treat them as properties of a certain kind. Then I give a bridge principle between the core notions of belief and belief-about before showing how the resulting view can be implemented in accordance with formal theories of syntax and semantics. I bring out some of the consequences this investigation has beyond our semantic theorizing and conclude, more generally, that any response to the puzzle requires paying some surprising cost or another.